Effect of Recombinant Human Growth Hormone (rhGH) Use on Genetic Methylation Patterns and Their Relationship with Body Composition in Small-for-Gestational-Age (SGA) Newborns - Juan M. Alfaro Velásquez; Elsa Maria Vásquez Trespalacios; Rodrigo Urrego; María C. Arroyave Toro; María del Pilar Montilla Velásquez; Cecilia Maria Díaz Soto; Juan C. Zuluaga Vélez; Verónica Jaramillo Henríquez; Jorge Emilio Salazar Flórez; Fernando P. Monroy; Hernando Alirio Palacio Mosquera; Sara Vélez Gómez; et al. (Biomedicines)
Background: Low birth weight in newborns is of multifactorial origin (fetal, maternal, placental, and environmental factors), and in one-third of cases, the cause is of unknown origin, with high infant morbidity and mortality. The main treatment for regaining weight and height in children with low birth weight is the application of growth hormones. However, their role as a protective factor to prevent an increase in body composition and the development of metabolic diseases is still poorly understood. Methodology: A case–control study was conducted in a cohort of patients consulted at the CES Pediatric Endocrinology Clinic, Medellín, Colombia, between 2008 and 2018. We evaluated sociodemographic and clinical variables. Additionally, the identification of differential patterns of genomic methylation between cases (treated with growth hormone) and controls (without growth hormone treatment) was performed. The groups were compared using Fisher’s exact test for qualitative variables and Student’s t-test for the difference in means in independent samples. The correlation was evaluated with the Pearson coefficient. Results: Regarding clinical manifestations, body mass index (BMI) was higher in children who did not receive growth hormone treatment, higher doses of growth hormone treatment helped reduce body mass index (R: −0.21, and p = 0.067), and the use of growth hormone was related to a decrease in triglyceride blood concentrations (p = 0.06); these results tended towards significance. Regarding genome-wide methylation patterns, the following genes were found to be hypermethylated: MDGA1, HOXA5, LINC01168, ZFYVE19, ASAH1, MYH15, DNAJC17, PAMR1, MROCKI, CNDP2, CBY2, ZADH2, HOOK2, C9orf129, NXPH2, OSCP1, ZMIZ2, RUNX1, PTPRS, TEX26, EIF2A4K, MYO1F, C2orf69, and ZSCAN1. Meanwhile, the following genes were found hypomethylated: C10orf71-AS1, ZDHHC13, RPL17, EMC4, RPRD2, OBSCN-AS1, ZNF714, MUC4, SUGT1P4, TRIM38, C3, SPON1, NGF-AS1, CCSER2, P2RX2, LOC284379, GGTA1, NLRP5, OR51A4, HLA-H, and TTLL8. Conclusions: Using growth hormone as a treatment in SGA newborns helps regain weight and height. Additionally, it could be a protective factor against the increase in adolescent body composition.